The encyclopedia of migration and minorities in Europe (New York ; Cambridge)
xxxix s., [2] s. harita, 768 s.
Keywords: "Although migration and integration have become important concepts today as a result of globalization, migration movements, integration, and multiculturalism have always been part of the history of Europe. Few people realize how many ethnic groups participated in migration within Europe or into Europe and this ignorance has grave consequences for the social and political status of immigrants. Newly available to an English-speaking audience, this encyclopaedia presents a systematic overview of the existing scholarship regarding migration within and into Europe. The first section contains survey studies of the various regions and countries in Europe covering the last centuries. The second section presents information on about 220 individual groups of migrants from the Sephardic Jews emigration from Spain and Portugal in the sixteenth and seventeenth centuries to the present-day migration of old-age pensioners to the holiday villages in the sun. The first resource of its kind, The Encyclopaedia of Migration and Minorities in Europe is a comprehensive and authoritative research tool." --